2020
DOI: 10.1007/s10877-020-00531-w
|View full text |Cite
|
Sign up to set email alerts
|

Study of early warning for desaturation provided by Oxygen Reserve Index in obese patients

Abstract: Acute hemoglobin desaturation can reflect rapidly decreasing PaO 2. Pulse oximetry saturation (SpO 2) facilitates hypoxia detection but may not significantly decrease until PaO 2 < 80 mmHg. The Oxygen Reserve Index (ORI) is a unitless index that correlates with moderately hyperoxic PaO 2. This study evaluated whether ORI provides added arterial desaturation warning in obese patients. This IRB approved, prospective, observational study obtained written informed consent from Obese (body mass index (BMI) kg m −2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
(54 reference statements)
0
17
1
Order By: Relevance
“…We think that the reason why they found the added warning time so long, unlike us, may be due to the fact that they performed the study in ASA I-II healthy individuals and that they had long (6 minutes) preoxygenation and ventilation times, which provide better oxygen reserve. [17]. In our study, we found these values to be shorter, unlike Tymbal et al We think that the reason for this is that we accepted 94%, not 95%, as the endpoint for alarm time for SpO 2 and included more obese (BMI > 40 kg/m2) patients in our study.…”
Section: Discussioncontrasting
confidence: 53%
“…We think that the reason why they found the added warning time so long, unlike us, may be due to the fact that they performed the study in ASA I-II healthy individuals and that they had long (6 minutes) preoxygenation and ventilation times, which provide better oxygen reserve. [17]. In our study, we found these values to be shorter, unlike Tymbal et al We think that the reason for this is that we accepted 94%, not 95%, as the endpoint for alarm time for SpO 2 and included more obese (BMI > 40 kg/m2) patients in our study.…”
Section: Discussioncontrasting
confidence: 53%
“…Our results on NIIB do not suggest that procedure time increases desaturation risk. Perioperative airway management and desaturation events are more frequent for obese patients [23] and are associated with a rapid decrease in oxygenation reserve [24] . Accordingly, supraglottic airway or tracheal intubation may be favorable for obese patients with difficult airway or obstructive sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative airway management and desaturation events are more frequent for obese patients [23] and are associated with a rapid decrease in oxygenation reserve. [24] Accordingly, supraglottic airway or tracheal intubation may be favorable for obese patients with difficult airway or obstructive sleep apnea. The required anesthetic depth for IBs is deeper than that for simple bronchoscopy requiring shorter time.…”
Section: Discussionmentioning
confidence: 99%
“…For impending hypoxemia , Tsymbal et al [ 22 ] studied 72 adult patients during induction of general anesthesia - of whom 36 were obese and 36 were non-obese. After pre-oxygenation and induction of general anesthesia, patients were kept apneic until SpO 2 dropped to 94%.…”
Section: Plethysmography: More Than Spo 2 Monitori...mentioning
confidence: 99%